Analysis of the Effect of Engineering Education in Nation Building in India - SINGH, MR. KARAMJEET (The journal of contemporary issues in business and government, 2021)
India has been a permanent member of the Washington Convention since 2014, and TIER-I institutions are required to promote universal accreditation, recognize qualifications, and establish connections with technical institutions around the world to obtain program accreditation. In additional words, technological institutions should struggle for the nonstop development of the numerous mechanisms of the machine: inputs, physical capitals, statistics, people, capital and resources, prospectus and learning processes, manufacturing, productivity, work-life relationships and feedback mechanisms. India offers the third largest network education, but faces accessibility, justice and affordability issues. The country's main challenges include: converting demographic income to demographic dividends, cumulative gross enrollment ratio (GER) for higher education, and equitable access to qualifying education in other provinces and distributions. The Indian government has taken a lot of steps in this course. For specimen, establishing the state accreditation committee as an independent body for launching teacher training, funding student projects, supporting ICT, etc. Also there is curriculum and development process for education connection with the working world, full use of equipment, research environment, recruitment in educational institutions, technical policy upgrade, raising standards and adopting an institutional approach to achieving excellence. This document aims to show such types of initiatives that can help organizations improve their efficiency and strive for excellence.